The Relationship Between Knowledge Level of Noise Exposure and the Pattern of Personal Listening Devices (PLDS) Usage - Layla Rahma Fauzia; Asti Kristianti; Sandi Lesmana Limanjaya Liem; Yanti Nurrokhmawati (Eduvest - Journal of Universal Studies, 2026)
This study examines the relationship between the level of knowledge about noise exposure and PLDs usage patterns among 2024 Cohort Medical Students, Faculty of Medicine, by describing PLD usage patterns based on user characteristics and type, duration of exposure, and volume of use. The study employs a descriptive analysis with a cross-sectional approach involving 154 students. This study uses the chi-square test, strengthened by the Spearman correlation test. The results showed that most students using PLDs were women (72.1%) and aged ≥18 years (94.2%). Knowledge levels were mostly categorized as good (86.4%). PLD usage patterns by type were predominantly in-ear (69.5%), with duration of exposure ≤60 minutes (58.4%) and volume ≤60% (81.8%). A significant relationship existed between knowledge level about noise exposure and PLD usage patterns [based on type (p = 0.006), duration of exposure (p = 0.001), and volume (p = 0.000)], with an odds ratio indicating that good knowledge was 214.5 times more likely to be associated with good usage patterns (OR > 1). The research analysis confirmed a relationship between knowledge level about noise exposure and PLD usage patterns.